2021
DOI: 10.1021/acs.inorgchem.1c03005
|View full text |Cite
|
Sign up to set email alerts
|

Computational Spectroscopy of the Cr–Cr Bond in Coordination Complexes

Abstract: We report the accurate computational vibrational analysis of the Cr–Cr bond in dichromium complexes using second-order multireference complete active space methods (CASPT2), allowing direct comparison with experimental spectroscopic data both to facilitate interpreting the low-energy region of the spectra and to provide insights into the nature of the bonds themselves. Recent technological development by the authors has realized such computation for the first time. Accurate simulation of the vibrational struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This would require 342 gradient calculations for 1 and 390 for 2 . Since our interest is focused on the geometric parameters within the first coordination sphere, partial Hessian vibrational analysis (PHVA) was performed including seven atoms (Mn and the first coordination sphere) for the high-spin and intermediate-spin states of both complexes . This reduced the number of gradient calculations to 42.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…This would require 342 gradient calculations for 1 and 390 for 2 . Since our interest is focused on the geometric parameters within the first coordination sphere, partial Hessian vibrational analysis (PHVA) was performed including seven atoms (Mn and the first coordination sphere) for the high-spin and intermediate-spin states of both complexes . This reduced the number of gradient calculations to 42.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Although not a spin-crossover complex, a very serious example of this can be seen in the metal–metal bonding in dichromium complexes. These complexes have very small energy differences between the bonding and antibonding orbitals, leading to significant populations in the antibonding orbitals that, in turn, means that a DFT calculation, assuming that all bonding orbitals are doubly occupied, cannot predict a reliable geometry. , This failure of DFT is due to its use of a single determinant and is well known to occur. In addition to these challenging examples, efforts have been made to improve DFT-computed geometries in spin-crossover complexes by “point-wise” CASPT2 calculations. , However, for low-symmetry or asymmetric complexes, this approach becomes tedious since the metal–ligand bond distances can no longer be stretched isotropically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm that XMS-CASPT2-optimized geometries are minima, full harmonic vibrational analyses (FHVA) were performed by means of a gradient finite difference for the S 0 , S 1 , and T 0 states of the bare copper corrole. Due to the large size of the triphenyl copper corrole, partial Hessian vibrational analysis (PHVA) 79 was performed for the S 0 and T 0 states. The three phenyl groups were not included in the vibrational analysis.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…39 Some studies in the literature have statistically proved that vertical excitation energies are indeed improved with IPEA shift. 40,41 It has also been reported that geometrical parameters 42,43 and molecular properties 44,45 may be improved. In spite of its potential utility, no analytic derivatives using IPEA shift have yet been developed; this may be partially due to the requirement for introducing an empirical parameter into "ab initio" methodology rather than technical difficulties.…”
Section: Introductionmentioning
confidence: 96%